A Latin American Reading of the Spiritual Exercises of Saint Ignatius - Ellacuría, Ignacio (Spiritus, 2010)
Spiritus 10 (2010): 205242 2010 by The Johns Hopkins University Press Ellacura | A Latin American Reading of the Spiritual Exercises of Saint Ignatius 206 Desert Cross Paul Elliot + Vatican II holds that in each sociocultural territory it is necessary to promote the kind of theological reection that subjects the actions and deeds revealed by God, as handed down to us by Sacred Scripture and explained by the Fathers and by the Churchs magisterium, to a new investigation, carried on in the light of the universal Church.2 + Medelln shows in the concrete the possibility and necessity of this his toricization of theology and pastoral practice in that which concerns Latin America, but since then a number of great difculties in this process have surfaced. [...]what we have here is the subversion of fundamental values of worldly cultures, of possessed cultures, and this cannot but lead to struggle and contradiction. The secular and Christian dynamisms tend to ow together in the third world.+ The demand for a concrete, secular action of liberation is uniquely united in the third world with the demand for a Christian action of liberation. this secular action cannot be the action consonant with develop mentalism, because historically this approach has caused the situa tion and, moreover, is based on values that are not Christian, In liberation theology there is a singular conuence. * Denunciation of unjust structures and persons, following upon an incarnation with the historical project of the poor. * Construction of new possibilities for humanization, starting from the specic historical situation. * Construction of a new human being in a new earth, which would be a mediation of the salvic presence of God. + Redemptive liberation is not an action that is purely secular; rather, it is a Christian action in the strict sense. The precise quotes: [...]whoever wishes to come with me must labor with me, so that through following me in the pain he or she may follow me also in the glory (95:5 from the address of the eternal King to a potential follower), and This will be to reect that all those who have judgment and reason will offer themselves wholeheartedly for this labor (96).]